Carbon nanotube materials for electrocardiography. Issue 5 (14th January 2021) - Kolanowska, Anna; Herman, Artur P.; Jędrysiak, Rafał G.; Boncel, Sławomir
Abstract : Carbon nanotubes as 1D nanomaterials of excellent physicochemical characteristics bring hope to compete and eventually conquer traditional solutions in electrocardiography – the most powerful non-invasive diagnostic tools in cardiac disorders. Abstract : Carbon nanotubes (CNTs) as 1D nanomaterials of excellent physicochemical characteristics bring hope to compete and eventually conquer traditional solutions in electrocardiography – one of the most powerful and non-invasive diagnostic tools in cardiac disorders. Our review tracks (from 2008) the development of CNTs as critical components in the systems where CNTs serve mainly as electroconductive fillers hence enable recording electrocardiographs (ECG). The characteristics of the CNT-based ECG systems – mainly to-skin electrodes and in a few cases wiring – covers their electrical and mechanical performance (adhesivity, flexibility, elasticity) and qualitative biocompatibility. By comprehensive analysis of the state-of-art in this field, we intend to indicate the most important challenges for the CNT (and other) materials to be applied in scale-up solution for electrocardiography in the near future.